2017
DOI: 10.18632/oncotarget.14469
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic control of human papillomavirus genome-containing cells is regulated by the function of the PDZ-binding motif of the E6 oncoprotein

Abstract: The function of a conserved PDS95/DLG1/ZO1 (PDZ) binding motif (E6 PBM) at the C-termini of E6 oncoproteins of high-risk human papillomavirus (HPV) types contributes to the development of HPV-associated malignancies. Here, using a primary human keratinocyte-based model of the high-risk HPV18 life cycle, we identify a novel link between the E6 PBM and mitotic stability. In cultures containing a mutant genome in which the E6 PBM was deleted there was an increase in the frequency of abnormal mitoses, including mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 56 publications
(97 reference statements)
1
12
0
Order By: Relevance
“…Therefore, BPVs may interfere with ACD homeostasis generating a pool of stem cells that may be predisposed to cell transformation. Such connections between ACD and PV tumorigenesis have begun to emerge from in vitro and in vivo models 53 – 56 although future studies are needed to gain insights into the relationship, if any, between PV-associated tumorigenesis and ACD perturbation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, BPVs may interfere with ACD homeostasis generating a pool of stem cells that may be predisposed to cell transformation. Such connections between ACD and PV tumorigenesis have begun to emerge from in vitro and in vivo models 53 – 56 although future studies are needed to gain insights into the relationship, if any, between PV-associated tumorigenesis and ACD perturbation.…”
Section: Discussionmentioning
confidence: 99%
“…A role for the E6 PBM in productive replication has also been observed for the high-risk types HPV31 and HPV16 [ 88 , 89 ]. More recent studies demonstrated that the E6 PBM protects the mitotic integrity of keratinocytes containing HPV18 episomes, with loss of the PBM domain leading to mitotic abnormalities that prevents the expansion of suprabasal cells to support vegetative viral replication [ 90 ]. What specific PDZ proteins are targeted by E6 to preserve mitotic integrity and to promote viral replication have yet to be defined.…”
Section: Maintenance Of Proliferative Potential In Differentiatingmentioning
confidence: 99%
“…The life cycle of HPVs is completely dependent on the differentiation program of the infected epithelium, and studies of infection in organotypic raft cultures show that viruses defective in binding the polarity proteins produce fewer progeny virus and their genomes are more unstable and prone to integration in the host DNA [56][57][58].…”
Section: Cell Polarity and The Hpv Life Cyclementioning
confidence: 99%